Medición de la atención en un call center usando box-jenkins - Raffo Lecca, Eduardo (2012)
The article reviews the concepts of prediction and presents a new methodology, which uses the Box- Jenkins class, for prediction of demand for calls, which make customers call centers known as callcenter. The study concludes that the use of time series tools, works efficiently, which would be in improving the efficiency and competitiveness in the call center.